Leaching of heavy metals from monolithic waste - Mizerna, Kamila; Król, Anna (Oficyna Wydawnicza Politechniki Wrocławskiej, 2018)
Leaching of heavy metals (Zn, Pb, Cu, Ni and Cr) from hazardous waste originating from steel works (slag) has been investigated. Contaminant leaching behavior from monolithic waste materials in the function of time was examined. There was established the cumulative leaching of elements per surface area of waste material and the impact of the duration of the leachant contact with the waste on the leachability. The types of processes accompanying the release of heavy metals were determined as well. Surface wash-off and dissolution were dominant processes during the leaching of the analyzed elements. Chromium was the only element whose release from the sample was controlled by diffusion when subjected to leaching in a liquid of pH 7. Due to the low levels of heavy metal leaching in relations to their concentrations in the samples, it seems that longer duration of the tank test can contribute to the release of additional amounts of the heavy metals.
Environment Protection Engineering. Vol. 44, 2018, nr 4, s. 143-158
Keywords: ochrona środowiska; inżynieria środowiska; czasopisma